Automatic Reading of ANCA-Slides: Evaluation of the AKLIDES System. (5th November 2012) - Damoiseaux, Jan; Mallet, Kathleen; Vaessen, Mia; Austen, Jos; Cohen Tervaert, Jan Willem
Abstract : The ANCA consensus prescribes screening by indirect immunofluorescence on neutrophils. We evaluated the first automated ANCA-pattern recognition system. C-ANCA ( n = 39 ) and P-ANCA ( n = 40 ) samples were selected from patients with ANCA-associated vasculitis (AAV). Non-AAV controls included sera from healthy controls ( n = 40 ), sera with possible interfering antibodies ( n = 46 ), or miscellaneous ANCA reactivity ( n = 31 ) . ANCA slides were analysed by AKLIDES and routine fluorescence microscopy. The C-ANCA pattern was recognized by routine microscopy in 92% and 97% on ethanol- and formalin-fixed slides, respectively. AKLIDES reported C-ANCA in 74% and 95%, respectively. P-ANCA was recognized by routine microscopy on ethanol-fixed neutrophils in 90%, while AKLIDES reported P-ANCA in 80%. Typically, only 65% and 33% of these samples showed the expected C-ANCA on formalin-fixed neutrophils by routine microscopy and AKLIDES, respectively. A C- or P-ANCA pattern was observed on ethanol-fixed neutrophils in 28% and 23% of the controls by routine microscopy and AKLIDES, respectively. Only 5% of the controls revealed C-ANCA on formalin-fixed neutrophils by routine microscopy and AKLIDES. Altogether, automated ANCA-pattern recognition by AKLIDES is promising. Distinction of C- and P-ANCA is good, but sensitivity on ethanol-fixed neutrophils needs improvement. When optimized, pattern recognition software may play an important role in AAV diagnostics.